PENGEMBANGAN MEDIA PEMBELAJARAN KARTU CERITA “KARCITA” DENGAN INTEGRASI MODEL STAD (STUDENT TEAMS-ACHIEVEMENT DIVISION) UNTUK MEMBACA PEMAHAMAN SISWA KELAS IV SDN SUGIHWARAS 01 - Salsabila, Afifah; Sri Maruti, Endang; Ma'rufah Rohmanurmeta, Fauzatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted due to the lack of reading comprehension skills of fourth grade elementary school students, which is seen from the students' difficulties in finding the main idea, understanding the content of the reading, and re-conveying the information that has been read. The purpose of the research is to develop a Story Card (KARCITA) learning media combined with the STAD learning model, with this being able to determine the level of feasibility or validity of media development, as well as testing its effectiveness in improving reading skills related to student understanding. The research method implemented is R&D which includes five stages, namely analysis, design, development, implementation, and evaluation. This study involved 20 fourth grade students of SDN Sugihwaras 01 as research subjects. Data collection in this study was carried out through observation, interviews, expert validation sheets, response questionnaires, and learning outcome tests. The results of the study showed that the KARCITA media obtained a very high level of validity, with a percentage of 94% based on the assessment of media experts. From the practical aspect, this media also obtained a very good category, which was indicated by the percentage of teacher responses of 97% and student responses of 93%. Meanwhile, the effectiveness of the media is seen from the increase in students' reading comprehension skills, which is indicated by an increase in the average score from 62.77 in the pretest stage to 94.95 in the posttest stage. Based on these findings, the KARCITA learning media combined with the STAD model is considered to meet the criteria of validity, practicality, and effectiveness so that it is suitable for use in improving the reading comprehension skills of fourth-grade elementary school students.